1999
DOI: 10.1111/j.0006-341x.1999.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

The Knox Method and Other Tests for Space‐Time Interaction

Abstract: The Knox method, as well as other tests for space-time interaction, are biased when there are geographical population shifts, i.e., when there are different percent population growths in different regions. In this paper, the size of the population shift bias is investigated for the Knox test, and it is shown that it can be a considerable problem. A Monte Carlo method for constructing unbiased space-time interaction tests is then presented and illustrated on the Knox test as well as for a combined Knox test. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
120
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 13 publications
0
120
0
Order By: Relevance
“…Some authors have suggested that shifts in the underlying population may artefactually cause space-time clustering. 27,28 We are not able to investigate population shifts, because this would require small area level population data for short time periods, which are not available in the United Kingdom. However, because space-time clustering was present in both the earlier and later parts of the study period (1987-1994 and 1995-2003), population shifts are unlikely to explain our results.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that shifts in the underlying population may artefactually cause space-time clustering. 27,28 We are not able to investigate population shifts, because this would require small area level population data for short time periods, which are not available in the United Kingdom. However, because space-time clustering was present in both the earlier and later parts of the study period (1987-1994 and 1995-2003), population shifts are unlikely to explain our results.…”
Section: Discussionmentioning
confidence: 99%
“…Knox's method is known to be subject to possible bias in case of nonuniform population shifts over the time period (Besag and Newell, 1991;Kulldorff and Hjalmars, 1999) and the probability to detect space -time clustering due to population shifts increases with the number of close pairs observed (Kulldorff and Hjalmars, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…If the population increases or decreases with different rates in different geographical areas, the test will be biased, and it is necessary to incorporate population-at-risk data in order to have a valid test (Kulldorff & Hjalmars 1999). Mantel (1967) generalized the Knox test to allow for an arbitrary decaying function of the spatial and temporal distance between events.…”
Section: Inferential Approaches For Space-time Clustersmentioning
confidence: 99%